The production of laboratory scientists: Negotiating membership and (re)producing culture - Zhang, Yifan (Frontiers in Education, 2022)
This ethnographic work is about the recruitment and enculturation of novice scientists in the laboratory. Interviews and participant observation were conducted in a biochemistry research lab at a small liberal arts college. I take a predominantly interpretive approach and ask the question of how novice scientists make sense of their decisions and behaviors as they gain membership into the laboratory and the community of scientists. Revising the value-neutral and the structure-centered depiction of science, I represent novice scientists as agents who are subjected to their sociohistorical positionalities but also who consciously maneuver with purpose and agenda. Novice scientists’ attempts to strategize and negotiate access to resources are epitomized by the culture of cold emailing. Additionally, I elucidate a process of how prospective medical students later gravitate to careers in science. While many initially anticipate a career in medicine, high retention in science has been observed when quality mentorship, friendly workplace culture, and supportive family members are present. I also present episodes of normative, value-laden practices—and how novices engage them—to capture the cosmology of scientists. I make the interpretation that the becoming of scientists is a rite of passage facilitated by behavioral habituation and values imprinting, via which cultural norms are transmitted and reproduced.